2020
DOI: 10.3390/ma13122802
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Bristle Stiffness of Polybutylene Terephthalate Manual Toothbrushes over 3 Months: A Randomized Controlled Trial

Abstract: We previously reported that polybutylene terephthalate (PBT) toothbrushes become less effective for plaque removal after two months of use. However, it remains unknown how the bristle stiffness of PBT toothbrushes changes after several months of use. We performed a single-center randomized controlled trial to evaluate the bristle stiffness and bristle splaying of soft and medium manual toothbrushes among dental and medical students of Hiroshima University. Subjects were 80 participants who met the criteria. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…ISO has specified a test method for measuring the resistance to deflection of the tufted portion of a conventional manual toothbrush [ 5 ]. In a previous study, we assessed the resistance to deflection of a PBT toothbrush in accordance with the ISO 22254 test method [ 6 ]. In this study, we found that the deflection of a single tuft of a PBT toothbrush can be measured using a soft-material bending-resistance tester.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ISO has specified a test method for measuring the resistance to deflection of the tufted portion of a conventional manual toothbrush [ 5 ]. In a previous study, we assessed the resistance to deflection of a PBT toothbrush in accordance with the ISO 22254 test method [ 6 ]. In this study, we found that the deflection of a single tuft of a PBT toothbrush can be measured using a soft-material bending-resistance tester.…”
Section: Discussionmentioning
confidence: 99%
“…The bristle stiffness of a toothbrush is associated with safe and effective toothbrushing [ 18 , 19 ]. In a recent study, we found that the bristle stiffness of a PBT toothbrush significantly decreased 2 months after use [ 6 ]. The bristle stiffness of a PBT toothbrush gradually decreased with use [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Periodontitis is a common infectious disease caused by periodontopathic bacteria with dysbiosis of the oral microbiota (1) and is associated with systemic diseases such as diabetes, cardiovascular disease and adverse pregnancy outcomes (2). For prevention of periodontitis, daily toothbrushing , flossing between teeth, promotion of oral hygiene, professional dental care and regular replacement of toothbrushes to avoid bristle splaying and softening are required (2)(3)(4)(5). Among periodontopathic bacteria, 'red complex' bacteria such as Porphyromonas gingivalis, Tannerella forsythia and Treponema denticola are major pathogens for chronic periodontitis (6).…”
Section: Introductionmentioning
confidence: 99%